Are carbon dots worth the tremendous attention it is getting: Challenges and opportunities. (March 2022) - Mandal, Saptarshi; Das, Prolay
Highlights: Amidst the rapid pace of publications, few fundamental problems on carbon dot (CD) are often disregarded and continued to be unanswered either consciously or unconsciously. The inconsistency in nomenclature has been elucidated. The negative impacts of diverse synthesis precursors and obscure purification procedures have been pointed out. The fluorescence mechanism of the CD has been summarized and the fallacy associated with this has been summarized. The nanotoxicity issue of CD has been explained. Doubts over the mesmeric applications of CD have been illuminated. An industrial outlook of the CD has been provided. Abstract: In the last decade, research on 'carbon dot' (CD) has grown exponentially with its exhilarating aspects in biomedical, environmental remediation, energy-related applications, and many others. However, with the rampant pace of publications, few rudimentary questions over this nanoparticle have been overlooked and continued to be unanswered either consciously or unconsciously. Naturally, it is fostering a negative impact on CD research and confining its enormous potential within the laboratory. Herein, we have tried to decode the interconnected factors that are shackling further growth or transition of CD to industry and ultimately to market. Towards this, we have explicated the inconsistent nomenclature, multifarious synthesis precursors and approaches, the ambiguities over purification, and the nature of fluorescence. We have also audited the nanotoxicity issue of CD and elucidated why CD is disparate from its counterparts over nanotoxicity issues. Then we raised questions with a few examples on otherwise so mesmeric applications of CD. In a first of its kind, we have provided an industrial outlook of the CD and delineated paths to break the barrier. Overall, we believe attention to a few fundamental concerns associated with CD will accelerate its transition to mankind. 〈PE-FRONTEND〉 Graphical abstract: Image, graphical abstract